Marapu: sistem ritual Kematian Pada Suku Loli, Kota Waikabubak, kabupaten Sumba Barat, Provinsi NTT dan potensinya sebagai sumber belajar sejarah - salman, jorghia; Pageh, I Made; Maryati, Tuty (Universitas Pendidikan Ganesha, 2024)
Abstract This research aims to find out: (1) why the Marapu death ritual system in the loli Tribe, waikabubak city, West Sumba regency, NTT Province still exists until now in the globalization era, (2) how is the process of the Marapu death ritual system in the Loli Tribe, Waikabubak city, West Sumba Regency, NTT Province, (3) what are the Marapu kamatian ritual systems that can be used as a learning resource. This research is a type of qualitative research using cultural anthropology research methods and religious systems through several steps, namely; (1) heuristics, (2) data validity checking, (3) data techniques and analysis. The results of this research show that; (1) the ritual of marapu's death is a relic of the ancestors of the loli people who are still guarded and preserved to this day, (2) The process of the marapu kematina ritual is carried out for three days and three nights and will be carried out by death, (3) aspects of the marapu death ritual that have the potential as a source of learning history, namely; aspects of knowledge, spiritual, social, heritage, historical which are arranged in the teaching module so that they can be used as a source of history learning. Keyword: